1988
DOI: 10.1056/nejm198809083191001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Human Granulocyte-Macrophage Colony-Stimulating Factor on Chemotherapy-Induced Myelosuppression

Abstract: An increase in the dose of chemotherapy enhances the response of many experimental and clinical cancers, but the extent of dose escalation is often limited by myelosuppression. In preliminary trials, recombinant human granulocyte-macrophage colony-stimulating factor (rhGM-CSF) has augmented leukocyte numbers and function, but the optimal dose is not established. We treated 16 adults who had inoperable or metastatic sarcomas with escalating doses of rhGM-CSF before and immediately after a first cycle of chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 636 publications
(114 citation statements)
references
References 22 publications
2
112
0
Order By: Relevance
“…Further support for a need to adjust the dose scheduling of cytokine intervention comes from other studies in which the utility of bone marrow transplant (BMT) to reduce RAIT-induced myelosuppression was evaluated. We found that the optimal window of efficacy varied from 2 to 3 days post-RAIT when using a 90 Y fragment, from 4 to 5 days for a 90 Y-IgG and from 6 to 8 days for an 131 I-IgG (Blumenthal et al, 1995a;Antman et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Further support for a need to adjust the dose scheduling of cytokine intervention comes from other studies in which the utility of bone marrow transplant (BMT) to reduce RAIT-induced myelosuppression was evaluated. We found that the optimal window of efficacy varied from 2 to 3 days post-RAIT when using a 90 Y fragment, from 4 to 5 days for a 90 Y-IgG and from 6 to 8 days for an 131 I-IgG (Blumenthal et al, 1995a;Antman et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…A randomised study would be necessary to confirm the relative benefits of the use of haemopoietic growth factors and ABMR following HDM. Effects of GM-CSF on platelet production have been seen previously in patients with myelodysplasia (Vadhan-Raj et al, 1988) and after chemotherapy (Antman et al, 1988) and could be anticipated from in vitro bone marrow culture experiments (Metcalf, 1985).…”
Section: Patientsmentioning
confidence: 70%
“…Several trials have shown that haemopoietic growth factors can reduce the myelotoxicity of chemotherapy (Bronchud et al, 1987;Antman et al, 1988;Morstyn et al, 1988) and we therefore decided to combine high-dose melphalan with GM-CSF for patients with metastatic colorectal carcinoma in the hope that we could obtain similar response rates to those of Leff et al…”
mentioning
confidence: 99%
“…It is secreted by activated T cells, endothelial cells, fibroblasts, and macrophages [4]. Due to its effect on hematopoietic cells, GM-CSF has been used to counter myelosuppression induced by high-dose chemotherapy, to bolster host defenses in immunocompromised states, and to accelerate recovery after bone marrow transplantation [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%